The relationship between incidence of pediculosis capitis and quality of life among female students at Madrasah Ulumul Quran (MUQ) Sigli - Mulki, Putria; Asrizal, Cynthia Wahyu; Maryam, Tjut; Hajar, Sitti; Putra, Teuku Romi Imansyah; Zulkifli, Baidillah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
Pediculosis capitis is an ectoparasitic disease that lives on the human scalp and caused by Pediculus humanus capitis. This incident is categorized as a neglected case, but the impact is quite significant. The incident can give a negative impact, including physical, psychological, social and school perceptions or learning impairment. This study aimed to determine the relationship between the incidence of pediculosis capitis with the quality of life of female students of Madrasah Ulumul Quran Sigli. This research is an observational analytic study with a cross-sectional approach. The samples were collected by the total sampling method. The results obtained from 155 respondents who met the inclusion criteria found that 124 respondents (80%) had pediculosis capitis and 31 respondents (20%) with no pediculosis capitis. Statistical analysis using the chi square test obtained a p value of 0.000 (0.05). The conclusion was found that there was a relationship between the incidence of pediculosis capitis and the quality of life of female students of Madrasah Ulumul Quran Sigli.